Malian Sahara : environment, people and prehistoric culture - (:unkn) unknown (My University, 1994)
The great moments of prehistoric occupation coincide with a series of favorable lacustrine episodes.Stations of the Lower Paleolithic, without going down beyond 19 ° N, show many affinities with the final Ugartian of the North-Western Sahara.The aterian industries are spread over three periods, between 40,000 and 20,000 years, the most recent of which also reaches the Azouad lake spreading.The Neolithic is established only at the end of the Holocene optimum. The tools show various influences. To the north, the facies of Oumm el Assel recalls the Neolithic productions of Capsian tradition. The facies of Hassi el Abiod, associated with a rich bone industry, in the region north-west of Araouane, is the work of African cro-magnoids (mechtoïdes). To the east, the facies of erg In-Sâkane is related to the Saharo-Sudanese Neolithic in Hoggar. It evolves with Proto-Mediterranean populations, at least from 4500 B.P. The Ounanian, between erg Foum el Alba and the cliff of Khnachich, may derive from industries of Ténéré. With the beginnings of aridification, the stations encroach on the previous deposits. The phenomenon is sensitive in the Pays rouge. In the plains and valleys north-west of the Iforas, an original culture of "sites with enclosures" is developing, where cattle farming is emerging. In addition to the Tilemsi, people are retreating to the shores of the new Inner Niger Delta. In Kobadi, in the Malian Sahel, we find the last representatives of African cro-magnoids, dating back to 3300 B.P., in a paleolacustrine context similar to that of Hassi el Abiod.
Keywords: African Research